Nonrelativistic supersymmetry in noncommutative space - Lozano, Gustavo Sergio (2005)
We analyze a model of nonrelativistic matter in (2+1)-dimensional noncommutative space. The matter fields interact with gauge fields whose dynamics is dictated by a Chern-Simons term. We show that it is possible to choose the coupling constants in such a way that the model has and extended supersymmetry and Bogomolnyi equations can be found.